2008
DOI: 10.1159/000178156
|View full text |Cite
|
Sign up to set email alerts
|

Basal Metabolic Rate and Body Composition in Patients with Post-Polio Syndrome

Abstract: The aim of this study was to compare basal metabolic rate (BMR) of post-polio syndrome (PPS) patients with healthy individuals and to determine its correlation to body composition. BMR (kcal/day) was determined by indirect calorimetry and body composition by dual energy X-ray absorptiometry. BMR was lower in the PPS patient group than in the control group, although it was similar in both groups when adjusted for body surface area, total body mass (TBM), lean body mass (LBM) and fat-free mass (FFM). PPS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The majority of studies (n = 5) found significant differences between the BMR and/or RMR of the 2 groups [9,26,27,28,29]. The BMR and/or RMR values were lower for the disabled subjects when expressed in absolute values; however, when adjusted for the FFM, this difference disappeared in half of the studies.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The majority of studies (n = 5) found significant differences between the BMR and/or RMR of the 2 groups [9,26,27,28,29]. The BMR and/or RMR values were lower for the disabled subjects when expressed in absolute values; however, when adjusted for the FFM, this difference disappeared in half of the studies.…”
Section: Resultsmentioning
confidence: 98%
“…Most of them were conducted in the USA [25,26,27], and there was 1 study each from Canada [9], Brazil [28] and Italy [29]. Four of the studies analyzed subjects with spinal cord injuries only [9,27,28,29], 1 evaluated spinal cord lesions and poliomyelitis impairment [29] and 1 evaluated patients with post-polio syndrome [28]. Three [9,27,29] included both male and female subjects, and the other 3 involved only male subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations